Interaction of nanoparticles with edible plants and their possible implications in the food chain - Rico, Cyren M. (2011)
The uptake, bioaccumulation, biotransformation, and risks of nanomaterials (NMs) for the food crops are still not well understood. Very few NMs and plant species have been studied, mainly at the very early growth stages of the plants. Most of the studies, except one with multiwalled carbon nanotubes performed on the model plant Arabidopsis thaliana and another with ZnO nanoparticles (NPs) on ryegrass, reported the effect of NMs on seed germination or 15 day old seedlings. Very few references describe the biotransformation of NMs in food crops and the possible transmission of the NMs to the next generation of plants exposed to NMs is unknown. The possible biomagnification of NPs in the food chain is also unknown.